THE EFFECT OF CARBON BLACK ON D.C. CONDUCTIVITY OF EPOXY RESIN - Ali, Ali S.; Majeed, Kawakib J. (European Scientific Journal, ESJ, 2013)
D.C conductivity of epoxy composites was determined as a function of carbon concentration and temperature in the range (301-401) K .The samples were prepared by hand lay up method with diferent black carbon weight percentage ratios (2.5%,5%, 7.5% and 10%) as sheets of dimensions(30x20x2)mm3 .The electrical conductivity has been measured as a function of temperature by using DC power supply PE-1540 ,digital electrometer Keithely 616 and electrical oven. It has been found that the increase in carbon concentration caused increase in DC conductivity at room temperatures (RT) to maximum value of 9.42x10-10 (Ω.cm)-1 for carbon weight percentage of (10%). The Hall mobility and carrier concentration at laboratory temperature has been calculated, the Hall mobility values are increased from 1.41 cm2/V.sec for the pure epoxy to 9.42cm2/V.sec for the composite with (10 wt %) C, and the carrier concentration values are increased from 4.2 x104 cm-3 for the pure epoxy to 6.4 x106 cm-3 for the composite with (10 wt %) C.